Three-silver high-transmittance coated glass capable of being tempered
By preparing a multi-layer film structure on Sanyin coated glass and using magnetron sputtering technology, combined with the use of ultraviolet curing layer, the problems of oxidation, film removal and scratching of Sanyin coated glass during processing are solved, and high light transmission, high heat insulation and excellent processing resistance are achieved, and are suitable for the applications of buildings and automobile doors and windows.
Patent Information
- Application Number
- CN202510046246.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
AI Technical Summary
The existing Sanyin-coated glass is prone to oxidation, film defiling and scratching during processing, resulting in fragile film quality and affecting its application in the construction and automobile energy-saving industries.
Multi-layer film structures are prepared in sequence on a glass substrate, including a transition layer of silicon-aluminum oxide, ATO dielectric layer, zinc-tin oxide seed layer, scandium alloy functional layer, nickel-chromium oxide barrier layer, etc., and a film layer is prepared by magnetron sputtering technology, combined with the use of the ultraviolet curing layer, the bonding force and processing resistance of the film layer are improved.
It realizes the high light transmission and high heat insulation properties of Sanyin coated glass, and at the same time improves its oxidation, scratch resistance and film removal resistance in the subsequent processing process, meeting the application needs of buildings and automobile doors and windows.
Smart Images

Figure CN119797779A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of low-radiation magnetron sputtering coated glass, and in particular provides a tempered triple-silver high-transmittance coated glass, which can be applied to the construction and automobile energy-saving industries. Background Art
[0002] Low-E coated glass is popular in the market because of its good energy-saving and decorative effects. At the same light transmittance, the heat insulation effect of triple-silver coated glass is far better than that of single-silver and double-silver coated products. As an energy-saving product with excellent heat insulation performance, triple-silver low-emissivity coated glass is of great significance to reducing energy consumption and carbon emissions.
[0003] Triple silver coated glass is a glass substrate that uses magnetron sputtering technology to prepare a nano-film layer, in which the Ag layer has a high reflective effect on mid- and far-infrared. However, as the silver layer thickens, due to the soft and easily oxidized nature of Ag itself, triple silver products are very prone to oxidation, film peeling and scratching during storage in the air and subsequent processing. In addition, as the silver layer thickens, in order to take into account the appearance and decorative effect, the dielectric layer is often thickened as well, which will cause excessive stress in the film layer, thereby affecting the bonding strength between the film layers.
[0004] At present, the existing triple silver products on the market have a relatively fragile film quality, which is prone to oxidation and scratches during subsequent cutting, edge grinding, cleaning, tempering and other processing. Therefore, how to avoid the above defects in the subsequent processing of triple silver products has become a problem that needs to be solved urgently in promoting triple silver energy-saving glass. Summary of the invention
[0005] The purpose of the present invention is to solve the deficiencies of the above-mentioned prior art and provide a tempered triple-silver high-transmittance coated glass.
[0006] The technical solution of the present invention is: A temperable triple-silver high-transmittance coated glass, characterized in that: a first transition layer / a first dielectric layer / a first seed layer / a first functional layer / a first barrier layer / a second transition layer / a second dielectric layer / a second seed layer / a second functional layer / a second barrier layer / a third transition layer / a third dielectric layer / a third seed layer / a third functional layer / a third barrier layer / a fourth transition layer / a fourth dielectric layer / a protective layer / a UV-curing layer are sequentially formed on a glass substrate.
[0007] Except for the outermost UV-curing layer of the coated glass which is prepared by roll coating and then cured by UV LED or the like, the remaining film layers are prepared by magnetron sputtering.
[0008] On the basis of the above technical solutions, there are the following further technical solutions: The first transition layer is silicon aluminum oxide with a thickness ranging from 10 to 20 nm; The first dielectric layer is ATO with a thickness of 10~20nm; The first seed layer is zinc tin oxide with a thickness ranging from 15 to 30 nm; The first functional layer is a silver-scandium alloy with a thickness ranging from 8 to 12 nm; The first barrier layer is nickel chromium oxide, and the thickness of the plating ranges from 0.5 to 0.8 nm.
[0009] Further: The second transition layer is AZO, and the thickness of the coating ranges from 10 to 20 nm; The second dielectric layer is ATO with a thickness of 15~60nm; The second seed layer is zinc tin oxide with a thickness ranging from 15 to 30 nm; The second functional layer is a silver-scandium alloy, and the plated thickness ranges from 12 to 15 nm; The second barrier layer is nickel chromium oxide, and the thickness of the plating ranges from 0.5 to 0.8 nm.
[0010] Further: The third transition layer is AZO, and the thickness of the coating ranges from 10 to 20 nm; The third dielectric layer is silicon oxynitride, and the thickness of the coating ranges from 25 to 60 nm; The third seed layer is zinc-aluminum oxide, and the thickness of the coating ranges from 10 to 20 nm; The third functional layer is silver-scandium alloy, with a plated thickness ranging from 14 to 17 nm; The third barrier layer is nickel-chromium, and the thickness of the plating ranges from 0.5 to 1 nm.
[0011] Further: The fourth transition layer is AZO, and the thickness of the coating ranges from 10 to 20 nm; / The fourth dielectric layer is aluminum silicon nitride, with a plating thickness of 15~20nm; / The protective layer is ZrO with a thickness ranging from 3 to 6 nm; / The UV curing layer is a polyurethane acrylic resin UV curing coating with a film thickness of 3~10μm.
[0012] The temperable triple silver high-transmittance coated glass is first coated with a layer of silicon oxide on the glass substrate. Since the coated silicon oxide is similar to the material of glass, it can greatly improve the bonding strength between the glass substrate and the film layer and reduce the problem of film removal. At the same time, similar optical constants have little effect on the color of the product.
[0013] The temperable triple silver high-transmittance coated glass is formed by reactive sputtering of pure zinc and pure tin targets in the seed layer. The power supply is co-sputtered, and the power supply duty cycle is set to adjust the sputtering time between the two targets, thereby flexibly controlling the chemical ratio in the film layer material to achieve the best ratio. By adjusting the ratio of zinc and tin materials in the film layer, the crystallization of the silver layer and the adhesion of the film layer are improved.
[0014] The temperable triple-silver high-transmittance coated glass uses a silver-scandium alloy in the functional layer, and the content of scandium accounts for 0.5% of the alloy composition. By uniformly doping a small amount of scandium metal in a pure silver target, the structure and performance of the functional layer can be greatly improved. Sc doping inhibits discontinuous Ag precipitation, resulting in a significant increase in hardness, while making the grains finer.
[0015] The temperable triple-silver high-transmittance coated glass uses a material with a certain conductivity, such as AZO and ITO, as a transition layer after the barrier layer. At the same time, since the target material is made of oxide, no or a small amount of oxygen can be introduced during the sputtering process, which can prevent the barrier layer from being over-oxidized. In addition, there is no need to design an air isolation pump position, saving the partition chamber of the coating room.
[0016] The temperable triple-silver high-transmittance coated glass has an outermost layer of UV-curing material rolled on it. After UV-hardening, the hardness and oxidation resistance of the coated glass surface are greatly improved, meeting the subsequent processing requirements such as cutting, grinding and washing steel.
[0017] The temperable triple-silver high-transmittance coated glass uses a large amount of oxides to reduce the absorption of the film material, and can prepare highly transparent triple-silver coated glass. The special protective coating also meets the processing requirements of subsequent cleaning and high-temperature tempering. It has excellent processing resistance. After tempering, the visible light transmittance of the glass is above 70%, and it has excellent thermal properties and processing resistance. The present invention adjusts the optical constants of the material through material selection, film layer structure design, film thickness optimization, etc., selects a strong protective layer, and prepares a highly transparent triple-silver coated product with excellent processing performance, which can be used in buildings and automobile doors and windows. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a structural diagram of the temperable triple-silver high-transmittance coated glass of the present invention; Glass substrate 2, first transition layer 3, first dielectric layer 4. First seed layer 5. First functional layer 6. First barrier layer 7. Second transition layer 8. Second dielectric layer 9. Second seed layer 10. Second functional layer 11. Third barrier layer 12. Third transition layer 13. third dielectric layer 14. third seed layer 15. third functional layer 16. third barrier layer 17. fourth transition layer 18. fourth dielectric layer 19. Wear-resistant protective layer 20. UV curing layer DETAILED DESCRIPTION
[0019] The present invention provides a temperable triple-silver high-transmittance coated glass, comprising a substrate glass, on which are sequentially formed: a first transition layer, a first dielectric layer, a first seed layer, a first functional layer, a first barrier layer, a second transition layer, a second dielectric layer, a second seed layer, a second functional layer, a second barrier layer, a third transition layer, a third dielectric layer, a third seed layer, a third functional layer, a third barrier layer, a fourth transition layer, a fourth dielectric layer, a protective layer, and an ultraviolet curing layer.
[0020] Except for the UV-cured layer, the remaining film layers are prepared by magnetron sputtering, which requires the background vacuum of the magnetron sputtering equipment to be 1*10 -6 Below mbar, process vacuum is 3~5*10 -3 The outermost UV-curing layer is a colorless and transparent layer that cures quickly after being irradiated by ultraviolet light to form a protective layer on the surface of the film.
[0021] The glass substrate is thoroughly cleaned by a cleaning machine with multiple disc brushes and roller brushes, dried by an air knife and then enters the vacuum coating chamber for sputtering with the participation of process gas. By controlling the reaction parameters of the sputtering process and adjusting the optical constants of the material, the desired film material is finally obtained.
[0022] The specific preparation process of the present invention is as follows: The first transition layer is silicon aluminum oxide with a thickness range of 10~20nm. It is formed by reactive sputtering of a rotating silicon aluminum target. The ratio of silicon aluminum target components is 90:10. The process gases introduced are Ar and O2, and the gas flow rates are 650:500sccm respectively. The main component of sputtering is silicon oxide material, and its refractive index n is between 1.48~1.52. There is a hysteresis effect in the silicon oxide sputtering process, so more reactive gas needs to be introduced to prevent the sputtering mode from reversing. This film layer is sputtered directly on the surface of the glass substrate. Since the first transition layer has a similar composition to that of glass, it can greatly improve the bonding force between the glass substrate and the film layer and reduce the problem of film stripping. At the same time, since the optical constants of the coated layer are similar to those of glass and the thickness is relatively thin, it has almost no effect on the color of the product.
[0023] The first dielectric layer is ATO with a thickness of 10-20 nm, prepared by sputtering a rotating ATO target, with Ar and O2 as process gases, and a gas flow rate of 1000:30 sccm. The main component is SnO2 doped with Sb2O3. The SnO2 material has a wider energy band width, so that the transmittance of the thin film material prepared therefrom is higher in the visible light range. At the same time, doping Sb2O3 can effectively change the electrical properties of the SnO2 thin film material and has little effect on its light transmittance.
[0024] The first seed layer is zinc tin oxide, which is formed by reactive sputtering of pure zinc and pure tin targets, with a thickness range of 15~30nm. As a seed layer, the different ratios of zinc and tin will directly affect the crystallization of the functional silver layer and the adhesion of the film layer. Through co-sputtering with power supply, setting the duty cycle, adjusting the sputtering time between the two targets, and then controlling the stoichiometric ratio in the film material to achieve the best ratio. The process gases introduced are Ar and O2, with gas volumes of 500:700sccm respectively.
[0025] The first functional layer is a silver-scandium alloy with a plated thickness range of 8-12nm. It is sputtered using a pulsed DC power supply to reduce the discharge pattern phenomenon common in triple-silver products. The process gas introduced is pure Ar with a gas volume of 800sccm and a process pressure of 3.5*10 -3 mbar, due to the soft texture of silver material, in order to obtain excellent thermal properties, the thickness of the silver layer will be greatly increased in the three-silver product. By uniformly doping a small amount of scandium metal in the pure silver target, the structure and performance of the functional layer can be greatly improved. Sc doping inhibits discontinuous Ag precipitation, resulting in a significant increase in hardness and making the grains finer.
[0026] The first barrier layer is nickel chromium oxide, with a plating thickness range of 0.5~0.8nm, and is formed by reactive sputtering using a nickel chromium target. It mainly protects the functional silver layer to prevent the silver layer from being over-oxidized and affecting the energy-saving effect of the product. The process gases introduced are Ar and O2, and the gas flow rates are 1000:30sccm respectively. Different products may require nickel chromium oxide with different oxygen contents. In high-transmittance three-silver products, the use of NiCr should be reduced, and the use of nickel chromium oxide can increase the transmittance of the product. However, nickel chromium oxide is prone to the risk of target poisoning during use, and the oxygen content should be properly controlled.
[0027] The second transition layer is AZO, and the coating thickness ranges from 10 to 20 nm. It is formed by sputtering an AZO ceramic target. The target material is composed of Al-doped ZnO. During the sputtering process, pure Ar is introduced as the process gas, and the gas flow rate is 1000 sccm. Since AZO has a certain conductivity, it can help reduce the resistance of the product. At the same time, since no or a small amount of oxygen is used during the sputtering process, the oxidation of the barrier layer and the silver layer can be reduced, thereby achieving a good protective effect.
[0028] The second dielectric layer is ATO with a thickness of 15-60nm, prepared by sputtering a rotating ATO target, with Ar and O2 as process gases, and a gas flow rate of 1000:30sccm. The main component is SnO2 doped with Sb2O3. The SnO2 material has a wider energy band width, so that the thin film material prepared therefrom has a higher transmittance in the visible light range. At the same time, doping Sb2O3 can effectively change the electrical properties of the SnO2 thin film material and has little effect on its light transmittance.
[0029] The second seed layer is zinc tin oxide, which is formed by reactive sputtering of pure zinc and pure tin targets, with a thickness range of 15~30nm. As a seed layer, the different ratios of zinc and tin will directly affect the crystallization of the functional silver layer and the adhesion of the film layer. Through co-sputtering with power supply, setting the duty cycle, adjusting the sputtering time between the two targets, and then controlling the stoichiometric ratio in the film material to achieve the best ratio. The process gases introduced are Ar and O2, with gas volumes of 500:700sccm respectively.
[0030] The second functional layer is a silver-scandium alloy with a thickness range of 12-15nm. It is sputtered using a pulsed DC power supply to reduce the common discharge pattern of three-silver products. The process gas introduced is pure Ar with a gas volume of 800sccm and a process pressure of 3.5*10 -3 mbar, due to the soft texture of silver material, in order to obtain excellent thermal properties, the thickness of the silver layer will be greatly increased in the three-silver product. By uniformly doping a small amount of scandium metal in the pure silver target, the structure and performance of the functional layer can be greatly improved. Sc doping inhibits discontinuous Ag precipitation, resulting in a significant increase in hardness and making the grains finer.
[0031] The second barrier layer is nickel chromium oxide, with a plating thickness range of 0.5~0.8nm, and is formed by reactive sputtering using a nickel chromium target. It mainly protects the functional silver layer to prevent the silver layer from being over-oxidized and affecting the energy-saving effect of the product. The process gases introduced are Ar and O2, and the gas flow rates are 1000:30sccm respectively. Different products may require nickel chromium oxide with different oxygen contents. In high-transmittance three-silver products, the use of NiCr should be reduced, and the use of nickel chromium oxide can increase the transmittance of the product. However, nickel chromium oxide is prone to the risk of target poisoning during use, and the oxygen content should be properly controlled.
[0032] The third transition layer is AZO, and the plating thickness ranges from 10 to 20 nm. It is formed by sputtering an AZO ceramic target. The target material is composed of Al-doped ZnO. During the sputtering process, pure Ar is introduced as the process gas, and the gas flow rate is 1000 sccm. Since AZO has a certain conductivity, it can help reduce the resistance of the product. At the same time, since no or a small amount of oxygen is used during the sputtering process, the oxidation of the barrier layer and the silver layer can be reduced, thereby achieving a good protective effect.
[0033] The third dielectric layer is silicon oxynitride, with a coating thickness range of 25~60nm, and is formed by reactive sputtering of a rotating silicon aluminum target. The silicon aluminum target component ratio is 90:10, and the process gases introduced are Ar, O2 and N2, with a gas flow rate of 1050:130:1050sccm. The main component of sputtering is silicon oxynitride material, which is very sensitive to oxygen content. The refractive index of the material can be changed by changing the oxygen flow rate introduced during the process. The refractive index "n" should decrease with the increase of the O2 flow rate. In order to make the process hysteresis-free, a sufficient amount of N2 needs to be introduced during the reaction. SiO x N y The refractive index of the material ranges from 1.8 to 1.9.
[0034] The third seed layer is zinc aluminum oxide, the thickness of the coating ranges from 10 to 20 nm, and is formed by reactive sputtering of a zinc aluminum target, and the process gas volume introduced is Ar and O2, the gas volume is 850:550 sccm, AlZnO x As the third seed layer, the functional Ag layer is deposited directly on the AlZnO x The metal barrier layer can be reduced, which can help the crystallization of the silver layer while improving the transmittance. However, there is a hysteresis phenomenon in the sputtering process of the ZnAl target. Under the premise of ensuring the sputtering rate, the amount of oxygen needs to be controlled to prevent it from reversing.
[0035] The third functional layer is a silver-scandium alloy, and the plated thickness ranges from 14 to 17 nm. It is sputtered using a pulsed DC power supply, which can reduce the discharge streaks common in three-silver products. The process gas introduced is pure Ar, the gas volume is 800 sccm, and the process pressure is 3.5*10-3mbar. Since the silver material is relatively soft, the three-silver product will greatly increase the thickness of the silver layer in order to obtain excellent thermal properties. By uniformly doping a small amount of scandium metal in the pure silver target, the structure and performance of the functional layer can be greatly improved. Sc doping inhibits discontinuous Ag precipitation, resulting in a significant increase in hardness, and at the same time makes the grains finer.
[0036] The third barrier layer is nickel-chromium, the thickness of the plating ranges from 0.5 to 1 nm, the process gas introduced is pure Ar, the gas volume is 800 sccm, and the process pressure is 3.5*10 -3 mbar, nickel-chromium has a good protective function. Plating nickel-chromium on the outermost barrier layer can prevent the silver layer from being over-oxidized by the atmospheric environment, thereby affecting the crystallization of the functional silver layer.
[0037] The fourth transition layer is AZO, and the plating thickness ranges from 10 to 20 nm. It is formed by sputtering an AZO ceramic target. The target material is composed of Al-doped ZnO. During the sputtering process, pure Ar is introduced as the process gas, and the gas flow rate is 1000 sccm. Since AZO has a certain conductivity, it can help reduce the resistance of the product. At the same time, since no or a small amount of oxygen is used during the sputtering process, the oxidation of the barrier layer and the silver layer can be reduced, thereby achieving a good protective effect.
[0038] The fourth dielectric layer is silicon aluminum nitride with a coating thickness of 15 to 20 nm. It is formed by reactive sputtering of a rotating silicon aluminum target. The silicon aluminum target composition ratio is 90:10. Ar and N2 are introduced into the process gas with gas flow rates of 500:600 sccm respectively. The main component of sputtering is silicon nitride material with a refractive index n of about 2.2. Silicon nitride has a high hardness and can be used as a dielectric layer to adjust the color of the product.
[0039] The wear-resistant protective layer is ZrO, with a plated thickness range of 3 to 6 nm, formed by reactive sputtering of a rotating zirconium oxide target. The selected target material is a ceramic target, and the process gas introduced is Ar and O2, with gas flow rates of 1000:40 sccm respectively. When using the target material, attention should be paid to the target rise slope, which is generally ≤200w / s. Since zirconium oxide ceramic materials have high toughness, high bending strength and high wear resistance, the film layer can be used as a wear-resistant protective layer to greatly improve the wear resistance of the product.
[0040] The UV curing layer is a roll-coated UV curing coating material, preferably a polyurethane acrylic resin and its additives, which can quickly cure the coating under UV light. The film thickness is 3-10 μm. The coating is prepared by roll coating to meet the fast transmission speed of the coating line. Finally, it is cured by UV LED lamp. The coating is transparent and colorless, and has almost no effect on the color of the coated glass itself. The cured coating can meet the processing requirements of cutting, grinding and washing steel and can be placed in the atmospheric environment for a short time.
[0041] The following is an explanation of a preferred embodiment. The detailed process parameters of the glass are shown in Table 1 and the optical parameters of the product are shown in Table 2.
[0042] Table 1 Process parameters of Example 1
[0043] Table 2 Optical parameters of the product in Example 1 before and after tempering
[0044] The existing triple-silver coated glass is prone to increase in resistance and decrease in visible light transmittance after tempering, indicating that the product is oxidized after tempering and has poor processing performance.
[0045] After the triple silver temperable coated glass of the present invention is tempered at high temperature in a tempering furnace, the phenomena shown are that the square resistance is reduced, the visible light transmittance is increased, and the post-tempering wiping test is qualified. After the product is tempered at high temperature, the resistance is reduced, indicating that the Ag layer of the product is crystallized again after tempering, and no oxidation phenomenon occurs, and the thermal performance is further improved. The visible light transmittance increases, and no fog defects appear on the surface, which also further indicates that the product can withstand high temperature treatment without oxidation.
[0046] The table shows the specific test data of the product. Because the current market also has corresponding demands for color, the data of glass surface reflection are listed to show that the color is a regular color.
[0047] Mechanism of no oxidation and scratches: Triple silver is easier to peel, scratch and oxidize than single and double silver. The main reason is that the silver layer is soft, the thickness of the silver layer increases significantly, and the film is soft. In addition, as the film thickness increases, in order to ensure high visible light transmittance, the corresponding barrier layer thickness decreases, the protective ability is weakened, and the silver layer is oxidized.
[0048] (1) The barrier layer NiCr has a protective effect on the Ag layer. The barrier layer reduces the amount of oxygen used and prevents excessive oxidation of nickel and chromium.
[0049] (2) In addition, since the Ag layer is soft, the Ag target is heavily doped with an alloy, and the doping of Sc inhibits the discontinuous Ag precipitation, resulting in a significant increase in hardness and making the grains finer.
[0050] (3) By co-sputtering pure zinc and pure tin targets, the composition ratio of the film layer is adjusted, so that the silver layer on the film is better crystallized and has better bonding strength.
[0051] (4) The use of ZrO increases the hardness of the film layer. Zirconium oxide has a high hardness, and the hardness of the film layer is significantly improved after plating.
[0052] (5) The outermost UV-curing layer uses the energy of ultraviolet photons to quickly cure the coating material to form a hard surface layer, thereby significantly improving the hardness of the material. In addition, the protective layer on the surface of the film can prevent oxygen from oxidizing the internal film layer.
[0053] Table 3 Process parameters of Example 2
[0054] Table 4 Optical parameters of the product in Example 2 before and after tempering
[0055] Table 5 Process parameters of Example 3
[0056] Table 6 Optical parameters of the product in Example 3 before and after tempering
Claims
1. A temperable triple-silver high-transmittance coated glass, characterized in that: The glass substrate is coated with: a first transition layer, a first dielectric layer, a first seed layer, a first functional layer, a first barrier layer, a second transition layer, a second dielectric layer, a second seed layer, a second functional layer, a second barrier layer, a third transition layer, a third dielectric layer, a third seed layer, a third functional layer, a third barrier layer, a fourth transition layer, a fourth dielectric layer, a protective layer, and an ultraviolet curing layer in sequence; Except for the outermost UV-curing layer which is prepared by roller coating and then cured by UV LED, the remaining coating layers are prepared by magnetron sputtering.
2. The temperable triple-silver high-transmittance coated glass according to claim 1, characterized in that: The first transition layer is silicon aluminum oxide with a thickness ranging from 10 to 20 nm; The first dielectric layer is ATO with a thickness of 10~20nm; The first seed layer is zinc tin oxide with a thickness ranging from 15 to 30 nm; The first functional layer is a silver-scandium alloy with a thickness ranging from 8 to 12 nm; The first barrier layer is nickel chromium oxide, and the thickness of the plating ranges from 0.5 to 0.8 nm.
3. The temperable triple-silver high-transmittance coated glass according to claim 2, characterized in that: The second transition layer is AZO, and the thickness of the coating ranges from 10 to 20 nm; The second dielectric layer is ATO with a thickness of 15~60nm; The second seed layer is zinc tin oxide with a thickness ranging from 15 to 30 nm; The second functional layer is a silver-scandium alloy, and the plated thickness ranges from 12 to 15 nm; The second barrier layer is nickel chromium oxide, and the thickness of the plating ranges from 0.5 to 0.8 nm.
4. The temperable triple-silver high-transmittance coated glass according to claim 3, characterized in that: The third transition layer is AZO, and the thickness of the coating ranges from 10 to 20 nm; The third dielectric layer is silicon oxynitride, and the thickness of the coating ranges from 25 to 60 nm; The third seed layer is zinc-aluminum oxide, and the thickness of the coating ranges from 10 to 20 nm; The third functional layer is silver-scandium alloy, with a plated thickness ranging from 14 to 17 nm; The third barrier layer is nickel-chromium, and the thickness of the plating ranges from 0.5 to 1 nm.
5. The temperable triple-silver high-transmittance coated glass according to claim 4, characterized in that: The fourth transition layer is AZO, and the thickness of the coating ranges from 10 to 20 nm; The fourth dielectric layer is aluminum silicon nitride, and the thickness of the coating is 15~20nm; The protective layer is ZrO, with a thickness ranging from 3 to 6 nm; The UV curing layer is a polyurethane acrylic resin UV curing coating, and the film thickness is 3~10μm.